Composite film and preparation method thereof, light-emitting device and display device

By using composite films made of group IIIA-VA compounds and bismuth-based compounds with doped elements in optoelectronic devices, the problem of corroding electrodes of hole functional layers is solved, and the lifetime of the light emitting device and the carrier injection capability are improved.

CN119836137APending Publication Date: 2025-04-15GUANGDONG JUHUA PRINTING DISPLAY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311331100.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing hole functional layer is prone to corrode the electrodes, resulting in poor lifespan of the optical device.

Method used

A composite film arranged in a laminated manner is used, the first film is made of a group IIIA-VA compound doped with the first doped element, and the second film is made of a bismuth-based compound doped with the second doped element. This structure improves the carrier implantation capability and the life of the light emitting device.

Benefits of technology

Through the use of doped elements, the carrier implantation capability and the life of the light emitting device are improved, the time for carrier implantation into the light emitting layer is delayed, and the service life of the light emitting device is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836137A_ABST
    Figure CN119836137A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photoelectric devices, and relates to a composite film which comprises a first film and a second film which are arranged in a stacked mode. The material of the first thin film is selected from IIIA-VA group compounds doped with a first doping element, the chemical formula of the IIIA-VA group compounds doped with the first doping element is AaT1-bXb, A is a IIIA group element, T is a VA group element, X is the first doping element, a is more than 0 and less than or equal to 1, b is more than or equal to 0.01 and less than or equal to 5, and the first doping element is a main group element; the material of the second thin film is selected from a bismuth compound doped with a second doping element, the chemical formula of the bismuth compound doped with the second doping element is BiXMyOz, Bi is the bismuth element, M is the second doping element, O is the oxygen element, x is larger than or equal to 1 and smaller than 3, y is larger than 0 and smaller than or equal to 1, z is larger than or equal to 1 and smaller than or equal to 6, and the second doping element is the main group element. The invention further relates to a preparation method of the composite film, a light-emitting device and a display device. According to the technical scheme provided by the invention, the carrier transmission capability can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of optoelectronic devices, and more specifically, to a composite film, a method for preparing the composite film, a light-emitting device, and a display device. Background Art

[0002] In recent years, with the rapid development of display technology, quantum dot light-emitting diodes (QLEDs) using semiconductor quantum dot materials as the light-emitting layer have received widespread attention. Their excellent characteristics such as high color purity, high luminous efficiency, adjustable luminous color and stable device make quantum dot light-emitting diodes have broad application prospects in the fields of flat panel display and solid-state lighting.

[0003] A hole injection layer of polyethylene dioxythiophene / polystyrene sulfonate (PEDOT:PSS) and a hole transport layer of TFB, PVK and other films are generally prepared on the existing ITO electrode. Although the HOMO energy level of PEDOT:PSS is well matched with the work function of ITO, enabling it to effectively inject and transport holes, PEDOT:PSS is acidic and has poor stability, and it is easy to corrode the electrode and the hole transport layer film, resulting in a poor life of the optical device. Summary of the invention

[0004] The technical problem to be solved by the embodiments of the present application is that the existing hole functional layer is prone to corrode the electrode, resulting in a short life of the optical device.

[0005] In order to solve the above technical problems, the present application provides a composite film, which adopts the following technical solution:

[0006] A composite film, comprising: a first film and a second film stacked together;

[0007] The material of the first film is selected from a IIIA-VA compound doped with a first doping element, wherein the chemical formula of the IIIA-VA compound doped with the first doping element is A a T 1-b X b , wherein A is a group IIIA element, T is a group VA element, X is a first doping element, and 0<a≤1,0.01≤b≤5, wherein the first doping element is a main group element;

[0008] The material of the second film is selected from a bismuth compound doped with a second doping element, wherein the chemical formula of the bismuth compound doped with the second doping element is Bi X M y O z , wherein Bi is a bismuth element, M is a second doping element, O is an oxygen element, and 1≤x<3, 0<y≤1, 1≤z≤6, wherein the second doping element is a main group element.

[0009] Further, the atomic radius of the second doping element is less than 1 angstrom; and / or,

[0010] The doping mass percentage of the second doping element is 1 to 10 wt %; and / or,

[0011] The thickness of the first film is in the range of 30 to 50 nm; and / or,

[0012] The thickness of the second film is in the range of 30 to 50 nm.

[0013] Further, the III-V group compound is selected from at least one of InP, InAs, InSb, A1N, AlP, AlAs, AlSb, GaN, GaP, A1NP, AlNAs, AlNSb, AlPAs, AlPSb, GaNP, GaNAs, GaPAs, GaPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNAs, GaAlN, GaAlPAs, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, and InAlNP; and / or,

[0014] The first doping element is selected from bismuth; and / or,

[0015] The second doping element is selected from Group IIIA elements, and the Group IIIA element is selected from one of boron, aluminum, gallium, indium, and thallium.

[0016] The present application also provides a method for preparing a composite film, which adopts the following technical solution:

[0017] A method for preparing a composite film comprises the following steps:

[0018] providing a substrate;

[0019] Providing a first ink, and forming a first thin film on the substrate by using the first ink, wherein the first ink comprises a IIIA-VA group compound doped with a first doping element and a solvent;

[0020] A second ink is provided, and a second thin film is formed on the first thin film by using the second ink, wherein the second ink comprises a bismuth compound doped with a second doping element and a solvent. Further, forming the first thin film on the substrate by using the first ink comprises the following steps:

[0021] adding a bismuth salt, a second doping element compound and a substituting element compound into a reaction solvent to form a bismuth-based compound precursor solution doped with the second doping element;

[0022] After the first treatment, a bismuth compound precipitate doped with the second doping element is obtained;

[0023] dissolving the bismuth-based layered compound precipitate doped with the second doping element in a solvent to form a second ink;

[0024] A second thin film is formed on the first thin film using the second ink.

[0025] Furthermore, the step of adding the bismuth salt, the second doping element compound, and the substituting element compound into a reaction solvent to form a bismuth-based compound precursor solution doped with the second doping element specifically includes:

[0026] dissolving the bismuth salt, the second doping element compound, and the substituting element compound in an acidic solution to form a mixed solution;

[0027] adding an alkaline solution to the mixed solution and stirring the mixed solution until it becomes a transparent liquid to form a bismuth-based compound doped with a second doping element;

[0028] or, dissolving a bismuth salt in an organic solvent to form a first solution;

[0029] Mixing the second doping element compound, the substituting element compound and the polar solvent to form a second solution;

[0030] After the first solution and the second solution are mixed, an alkaline solution is added to the mixed solution to form a bismuth-based compound precursor solution doped with the second doping element.

[0031] Further, the bismuth salt is selected from at least one of bismuth phosphate and bismuth sulfate; and / or,

[0032] The substituent element compound is selected from a vanadium compound and a silicon compound; and / or,

[0033] The second doping element compound is selected from a boron compound, an aluminum compound, and a gallium compound; and / or,

[0034] The solvent is selected from at least one of methanol, ethanol, ethylene glycol, glycerol, butanol, DMF, DMSO and / or

[0035] The organic solvent is selected from at least one of a glycerol aqueous solution and concentrated nitric acid; and / or,

[0036] The polar solvent is selected from at least one of deionized water and ammonia water; and / or,

[0037] The alkaline solution is selected from at least one of sodium hydroxide solution, potassium hydroxide solution or lithium hydroxide.

[0038] The present application also provides a light emitting device, which adopts the following technical solution:

[0039] A light-emitting device, comprising an anode layer, a composite film layer, a light-emitting layer, a composite film layer, and a cathode stacked in sequence; or

[0040] comprising an anode layer, a light-emitting layer, a composite film layer, and a cathode layer stacked in sequence; or

[0041] It includes an anode layer, a composite film layer, a light-emitting layer, a composite film layer, and a cathode layer stacked in sequence;

[0042] Wherein, the composite film layer is prepared by using the composite film or the composite film preparation method.

[0043] Further, the material of the anode layer and / or cathode layer includes one or more of metal, carbon material and metal oxide, the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or,

[0044] The light-emitting layer is a quantum dot light-emitting layer or an organic light-emitting layer; wherein the material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are respectively selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, wherein the II-VI group compounds include but are not limited to CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, Cd One or more of SeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and Group IV-VI compounds include but are not limited to SnS, SnSe, Sn Te, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, III-V compounds include but are not limited to GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, One or more of AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is, but is not limited to, at least one of CuInS2, CuInSe2 and AgInS2;The material of the organic light-emitting layer includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diarylanthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives.;

[0045] The present application also provides a display device, which adopts the following technical solution:

[0046] A display device comprises the light emitting device as described above.

[0047] Compared with the prior art, the embodiments of the present application have the following beneficial effects:

[0048] The composite film of the present application includes a IIIA-VA group compound doped with a first doping element as the first film to improve the carrier injection capability, and doping with the IIIA-VA group compound to produce an indirect band gap to limit the Auger recombination probability of the carriers; in addition, the composite film also includes a second film prepared by a bismuth-based compound doped with a second doping element to improve the life of the light-emitting device. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the scheme of the present application, a brief introduction is given below to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0050] Figure 1 is a flow chart of a method for preparing a composite film according to an embodiment of the present application;

[0051] Figure 2 yes Figure 1 A flowchart of a specific implementation of step S20;

[0052] Figure 3 yes Figure 1 A flowchart of a specific implementation of step S30;

[0053] Figure 4 is a schematic structural diagram of a light-emitting device according to an embodiment of the present application;

[0054] Figure 5It is a life curve diagram of the optical device of Example 1 of the present application and the optical device of Comparative Example 1.

[0055] Reference numerals:

[0056] 1. Substrate; 2. Anode; 3. Hole functional layer; 31. First film; 32. Second film; 4. Light-emitting layer; 5. Electron transport layer; 6. Cathode; 7. Encapsulation layer. DETAILED DESCRIPTION

[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.

[0058] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0059] An embodiment of the present application provides a composite film, including a first film and a second film that are stacked. In this embodiment, the first film is disposed on an anode layer.

[0060] The material of the first film is selected from a IIIA-VA compound doped with a first doping element, wherein the chemical formula of the IIIA-VA compound doped with the first doping element is A a T 1-b X b , wherein A is a group IIIA element, T is a group VA element, X is a first doping element, and 0<a≤1, 0.01≤b≤5, wherein the first doping element is a main group element.

[0061] The material of the second film is selected from a bismuth compound doped with a second doping element, wherein the chemical formula of the bismuth compound doped with the second doping element is Bi X M y O z, wherein Bi is a bismuth element, M is a second doping element, O is an oxygen element, and 1≤x<3, 0<y≤1, 1≤z≤6, wherein the second doping element is a main group element.

[0062] The carrier functional layer provided in the embodiment of the present application includes a IIIA-VA group compound doped with a first doping element as a first film to improve the carrier injection capability, and by doping the IIIA-VA group compound to form an indirect band gap, the Auger recombination probability of the carriers is limited; in addition, the composite film also includes a second film prepared by a bismuth-based compound doped with a second doping element, thereby improving the life of the light-emitting device.

[0063] In some embodiments, the IIIA-VA Group compound is selected from at least one of InP, InAs, InSb, A1N, AlP, AlAs, AlSb, GaN, GaP, A1NP, AlNAs, AlNSb, AlPAs, AlPSb, GaNP, GaNAs, GaPAs, GaPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNAs, GaAlN, GaAlPAs, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, and InAlNP.

[0064] In some embodiments, the material of the first film is a IIIA-VA group compound containing indium, selected from one of InP, InAs, and InSb. In this embodiment, the first film is preferably made of InP material.

[0065] The first film of the embodiment of the present application is arranged on the anode layer. Since the anode layer contains indium element, the first film prepared by using indium-containing IIIA-VA group compounds can reduce the interface difference with the anode layer, reduce the thermal and electrical differences, and will not damage the electrode substrate.

[0066] In some embodiments, the first doping element is bismuth, and the doping of bismuth increases the self-selected orbital splitting energy of IIIA-VA compounds, so that the doped IIIA-VA compounds have an indirect band gap to limit the Auger recombination probability of carriers.

[0067] In some embodiments, the atomic ratio of bismuth to VA element in the IIIA-VA compound doped with the first doping element is 1% to 5%. In this embodiment, the carrier injection layer is made of InP material, the VA element of the carrier injection layer is phosphorus, and the atomic ratio of bismuth to phosphorus in the InP material after doping is 1% to 5%. The carrier injection layer material after doping is InP (1-a) Bi a, where 0.01≤a≤0.05, for example: InP 0.99 Bi 0.01 、InP 0.98 Bi 0.02 、InP 0.97 Bi 0.03 、InP 0.96 Bi 0.04 、InP 0.95 Bi 0.05 .

[0068] In some embodiments, the thickness of the first film ranges from 30 to 50 nm, for example, 30 nm, 35 nm, 40 nm, 45 nm, or 50 nm.

[0069] In the embodiment of the present application, bismuth is doped to improve the carrier injection capability, and the bismuth element is used to increase the spin-orbit splitting energy, so that InP (1-a) Bi a An indirect band gap appears to limit the Auger recombination probability of carriers. The atomic ratio of bismuth to phosphorus in the doped InP material is 1% to 5%. If the atomic ratio of bismuth to phosphorus is lower than 1%, it will not play a role in improving the carrier injection capability. If the atomic ratio of bismuth to phosphorus is higher than 5%, local enrichment will easily occur, hindering the movement of carriers, thereby reducing the carrier injection capability.

[0070] In some embodiments, the material of the second film is selected from a bismuth compound doped with a second doping element, wherein the chemical formula of the bismuth compound doped with the second doping element is Bi X M y O z , wherein Bi is a bismuth element, M is a second doping element, O is an oxygen element, and 1≤x<3, 0<y≤1, 1≤z≤6;

[0071] In some embodiments, the thickness of the second film ranges from 30 to 50 nm, for example, 30 nm, 35 nm, 40 nm, 45 nm, or 50 nm.

[0072] The material of the second film in the embodiment of the present application is selected from bismuth compounds, and the layered structure of the bismuth compounds is used to make it easy for carriers to migrate to the surface, thereby improving the carrier transmission capacity. (1-a) Bi a Therefore, the use of bismuth-based compounds can reduce interface defects between the first film and the second film, reduce thermal and electrical differences, and prevent the first film from damaging the second film.

[0073] In some embodiments, the second doping element of the second film is selected from Group IIIA elements, and the atomic radius of the second doping element is less than 1 angstrom; the Group IIIA element is selected from one of boron, aluminum, and gallium. In the present embodiment, the second doping element is boron, and the atomic radius of the boron atom is smaller than the atomic radius of the vanadium atom.

[0074] In some embodiments, the bismuth-based compound before doping is selected from at least one of BiVO4 and Bi2SiO5. The bismuth-based compound after doping with the second doping element replaces the original vanadium (V) or silicon (Si). In this embodiment, the atomic radius of the boron (B) element is smaller than that of the vanadium element or the silicon element. Therefore, the bismuth-based compound doped with the second doping element enables the composite film to utilize its own hierarchical structure and low doping atomic radius to cause structural distortion of the composite material, thereby promoting carrier transport capability.

[0075] The life of a light-emitting device depends on the brightness rise stage and the brightness decay stage under a constant current density. The brightness rise stage is mainly due to the process of waiting for hole injection after the quantum dot absorbs an electron, which is called a negatively charged quantum dot QD-. In the brightness decay stage, the negatively charged quantum dot QD- absorbs holes to form QD excitons, and the QD exciton decays. Therefore, the method to improve the life of a light-emitting device is mainly to delay the injection of holes into the negatively charged quantum dot QD- and delay the decay process of the QD exciton.

[0076] The present application adopts boron as the second doping element of the bismuth-based compound, and the atomic radius of the boron atom is smaller than the atomic radius of the vanadium atom, so that the bismuth-based compound after doping with the second doping element has more localized defect states, so that the second film can temporarily capture carriers to delay the time for carriers to travel from the second film to the quantum dot layer, thereby delaying the time for carriers to be injected into the negatively charged quantum dots QD-, thereby increasing the duration of the brightness rise stage in the life curve of the light-emitting device, and thereby increasing the life of the light-emitting device.

[0077] In some embodiments, the doping mass percentage of the second doping element of the second film is 1 to 10 wt%. In this embodiment, the doping mass percentage of the boron element is 1 to 10 wt%, for example: 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%.

[0078] The boron doping mass percentage of the bismuth-based compound of the embodiment of the present application is 1-10wt%, which can cause the second film to be twisted and distorted, thereby improving the carrier mobility and enabling the carrier transport layer to have the ability to temporarily capture carriers. If the boron doping mass percentage is too low, the carrier transport layer cannot be twisted and distorted. If the boron doping mass percentage is too high, more BO will appear in the bismuth-based layered compound. 4- , forming too many defect states, which causes the second film to capture carriers, reducing the number of carriers entering the quantum dot layer, resulting in an imbalance between the hole transmission and electron transmission in the quantum dot layer, and an increase in negatively charged quantum dots QD-, which can easily cause damage to the light-emitting device.

[0079] See also Figure 1 As shown, the embodiment of the present application also provides a method for preparing a composite film, comprising the following steps:

[0080] Step S10, providing a substrate.

[0081] Step S20, providing a first ink, and forming a first thin film on the substrate using the first ink.

[0082] In this embodiment, the first ink includes a IIIA-VA compound doped with a first doping element and a solvent. Step S30, providing a second ink, and forming a second film on the first film by using the second ink.

[0083] In this embodiment, the second ink includes a bismuth-based compound doped with a second doping element and a solvent.

[0084] See also Figure 2 As shown, in some embodiments, the first film is formed on the anode by molecular beam epitaxy, and the IIIA-VA group compound doped with the first doping element is InX (1-a) Bi a The step S20, forming a first thin film on the substrate by using the first ink, comprises the following steps:

[0085] Step S21, placing the substrate in a molecular beam epitaxy device.

[0086] In this embodiment, the vacuum degree in the molecular beam epitaxy equipment is adjusted to 4×10 4 ~8×10 4 Pa.

[0087] Step S22, growing InT on the substrate by molecular beam epitaxy (1-a) Bi a , to form a first thin film, wherein the T element is selected from one of phosphorus, arsenic, and antimony, and 0.01≤a≤0.05.

[0088] In this embodiment, the T element is selected from phosphorus, and the step S22 is to grow InT on the substrate by molecular beam epitaxy. (1-a) Bi a , to form a first thin film, specifically comprising the following steps:

[0089] The phosphine valve is opened, and the temperature in the molecular beam epitaxy device is adjusted to 1000° C. to decompose the phosphine into phosphorus gas.

[0090] The temperature in the molecular beam epitaxy equipment was adjusted to 350-450°C.

[0091] The indium furnace and the bismuth furnace are turned on, and the indium beam and the bismuth beam are formed by the beam source furnace of the molecular beam epitaxy equipment and sprayed onto the substrate, wherein the temperature range of the indium beam is 800-1000° C., and the temperature range of the bismuth beam is 450-550° C.

[0092] In 4×10 4 ~8×10 4 InP was grown on the substrate at a growth rate of 10 nm / min in a phosphorus atmosphere with a pressure of Pa. (1-a) Bi a , forming a first thin film.

[0093] The embodiment of the present application controls the temperature in the molecular beam epitaxy equipment and adjusts the opening and closing of the bismuth furnace to regulate the deposition amount of bismuth and phosphorus elements, thereby regulating the doping ratio of the bismuth element to avoid the atomic ratio of bismuth and phosphorus being too large, which would lead to local enrichment and hinder the movement of carriers.

[0094] Please review Figure 1 As shown, in step S30, a second thin film is formed on the first thin film by using the second ink, wherein the second ink includes a bismuth-based compound doped with a second doping element and a solvent.

[0095] In some embodiments, step S30, forming a second film on the first film by using the second ink, specifically includes the following steps:

[0096] Step S31, adding a bismuth salt, a second doping element compound, and a substituting element compound into a reaction solvent to form a bismuth-based compound precursor solution doped with the second doping element;

[0097] In this embodiment, the atomic radius of the substituting element of the substituting element compound is greater than the atomic radius of the second doping element of the second doping element compound; the bismuth salt is selected from at least one of bismuth phosphate and bismuth sulfate; the substituting element compound is selected from one of a vanadium compound and a silicon compound; and the second doping element compound is selected from one of a boron compound, an aluminum compound, and a gallium compound.

[0098] In this embodiment, step S31, adding a bismuth salt, a second doping element compound, and a substituting element compound into a reaction solvent to form a bismuth compound precursor solution doped with the second doping element, specifically includes the following steps:

[0099] The bismuth salt, the second doping element compound and the substituting element compound are dissolved in an acidic solution to form a mixed solution.

[0100] An alkaline solution is added to the mixed solution, and the mixture is stirred until a transparent liquid is obtained to form a bismuth-based compound precursor solution doped with the second doping element.

[0101] In this embodiment, the bismuth salt is Bi(NO3)3, the substituent element compound is the vanadium compound NH4VO3, the second doping element compound is the boron compound NaBO2, the acidic solution is nitric acid, and the alkaline solution is uric acid, wherein the atomic radius of the vanadium atom is greater than the atomic radius of the boron atom. In this embodiment, uric acid is added to the mixed solution to convert the mixed solution into a weak alkaline solution and form a fine precipitate, so as to facilitate the precipitation of the bismuth compound.

[0102] In other embodiments, the step 31 of adding the bismuth salt, the second doping element compound, and the substituting element compound into the reaction solvent to form a bismuth-based compound precursor solution doped with the second doping element may further include the following steps:

[0103] dissolving a bismuth salt in an organic solvent to form a first solution;

[0104] Mixing the second doping element compound, the substituting element compound and the polar solvent to form a second solution;

[0105] After the first solution and the second solution are mixed, an alkaline solution is added to the mixed solution to form a bismuth-based compound precursor solution doped with the second doping element.

[0106] Among them, the bismuth salt is bismuth nitrate (Bi(NO3)3), the organic solvent is glycerol aqueous solution or concentrated nitric acid, the second doping element compound is sodium orthovanadate (NaVO4) or ammonium metavanadate (NH4VO3), the substituent element compound is a carbon-containing compound (sodium acetate (CH3COONa)) or a nitrogen-containing compound (urea (CO(NH2)2)), the polar solvent is deionized water or ammonia water, and the alkaline solution is sodium hydroxide solution.

[0107] When the substituting element compound is a carbon-containing compound (sodium acetate (CH3COONa)), bismuth nitrate is dissolved in a glycerol aqueous solution and recorded as the first solution; NaVO4 and sodium acetate are dissolved in deionized water and recorded as the second solution, and the second solution is slowly added to the first solution.

[0108] After mixing and stirring for 30 minutes, NaOH is added to adjust to an alkaline solution to form a bismuth-based compound precursor solution doped with the second doping element.

[0109] When the substituting element compound is a nitrogen-containing compound (urea (CO(NH2)2)), bismuth nitrate is dissolved in concentrated nitric acid and magnetically stirred for 30 minutes to obtain a first solution; ammonium metavanadate is dissolved in aqueous ammonia solution, urea is added in a molar ratio of N to V of 1:10, and magnetically stirred for 30 minutes to obtain a second solution, and the first solution is slowly added to the second solution.

[0110] After mixing, the mixture was continuously stirred magnetically for 1 hour, NaOH was added to adjust the mixture to an alkaline solution, and ultrasonic treatment was performed for 30 minutes to form a precursor solution of a bismuth-based compound of a second doping element.

[0111] Step S32: After the first treatment, a bismuth-based compound precipitate doped with a second doping element is obtained.

[0112] In some embodiments, the first treatment includes the following steps: adjusting the temperature to a set temperature and stirring for a set time; wherein the set temperature is 80-90° C., and the set time is 24 hours.

[0113] After cooling to room temperature, filtering is performed to obtain a bismuth compound precipitate doped with the second doping element; wherein the bismuth compound precipitate doped with the second doping element is a yellow precipitate of BiVO4 doped with the second doping element by boron element.

[0114] Step S33 , dissolving the bismuth-based compound precipitate doped with the second doping element in an ethanol solution to form a second ink.

[0115] In this embodiment, the yellow BiVO4 precipitate doped with the second doping element by the boron element is washed and dried and then dissolved in an ethanol solution to form the second ink.

[0116] Step S34, disposing the second ink on the first film to form the second film.

[0117] The embodiment of the present application prepares the second film on the first film by a solution method, which simplifies the production process and can control the doping ratio of the second doping element according to the ratio of the added components during the preparation of the second ink, so as to obtain a bismuth-based compound doped with boron element with a doping mass percentage of 1 to 10wt%.

[0118] The composite thin film prepared by the composite thin film preparation method provided in the embodiment of the present application can promote the rapid transmission of carriers, so that the carriers can be quickly transmitted to the interface of the light-emitting layer and can be delayed in being injected into the light-emitting layer, thereby increasing the duration of the brightness rising stage in the life curve of the light-emitting device, thereby increasing the life of the light-emitting device.

[0119] See also Figure 4 As shown, the embodiment of the present application also provides a light-emitting device, including a stacked anode layer, a composite film layer, a light-emitting layer, and a cathode layer; or including a stacked anode layer, a light-emitting layer, a composite film layer, and a cathode layer; or

[0120] It includes an anode layer, a composite film layer, a light-emitting layer, a composite film layer, and a cathode layer which are stacked in sequence.

[0121] Wherein, the composite film layer is prepared by the composite film as described above or by the preparation method of the composite film as described above.

[0122] In this embodiment, the light-emitting device is a positive structure, including a substrate 1, an anode 2, a hole functional layer 3, a light-emitting layer 4, an electron transport layer 5, a cathode 6, and an encapsulation layer 7 stacked on the substrate from bottom to top, wherein the hole functional layer 3 adopts the composite film as described above.

[0123] The hole functional layer 3 includes a first thin film 31 and a second thin film 32 which are stacked, wherein the material of the first thin film 31 is selected from an indium-containing IIIA-VA group compound doped with bismuth, and the atomic ratio of bismuth to VA group elements in the doped indium-containing IIIA-VA group compound is 1% to 5%, and the thickness of the first thin film ranges from 30 to 50 nm, for example, 30 nm, 35 nm, 40 nm, 45 nm, and 50 nm.

[0124] The material of the second film 32 is selected from a bismuth-based compound doped with a second doping element. In the present embodiment, the second doping element is boron. The doping mass percentage of boron in the doped bismuth-based compound is 1 to 10 wt %. The thickness of the second film ranges from 30 to 50 nm, for example, 30 nm, 35 nm, 40 nm, 45 nm, and 50 nm.

[0125] The light-emitting layer 4 is a quantum dot light-emitting layer or an organic light-emitting layer; the material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot, a core-shell structure quantum dot, a quantum dot based on a gradient shell, a phosphorescent or fluorescent light-emitting material, and the material of the single structure quantum dot, the core material and the shell material of the core-shell structure quantum dot are selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, Hg At least one of Te, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, wherein the IV-VI group compound is selected from SnS , SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, and the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, Al At least one of NAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2;

[0126] The material of the organic light-emitting layer includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distyrene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives.

[0127] The material of the electron transport layer 5 includes inorganic materials and / or organic materials; the inorganic material is selected from one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements include one or more of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material is selected from one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds.

[0128] The material of the anode layer 2 and / or the cathode layer 6 includes one or more of metals, carbon materials and metal oxides, the metals include one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon materials include one or more of graphite, carbon nanotubes, graphene and carbon fibers; the metal oxides include doped or undoped metal oxides, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or include a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2.

[0129] In the embodiment of the present application, the first film is prepared by doping the indium IIIA-VA group compound containing bismuth element, and has good interface properties with the indium-containing anode layer, reducing the thermal and electrical differences. The first film will not damage the electrode substrate, and the first film is doped with bismuth element to improve the hole injection ability; the second film is prepared by doping the bismuth compound with boron element, and has good interface properties with the first film, reducing the thermal and electrical differences. The first film will not damage the second film, and the second film is doped with boron element to make the doped bismuth compound have more local defect states, so that the second film can temporarily capture hole carriers to delay the time for holes to be injected from the second film to the quantum dot layer, thereby delaying the time for holes to be injected into the negatively charged quantum dots QD-, thereby increasing the duration of the brightness rising stage in the life curve of the light-emitting device, and thus increasing the life of the light-emitting device.

[0130] The above scheme is further described below in conjunction with specific embodiments. The preferred embodiments of the present invention are described in detail as follows:

[0131] Embodiment 1:

[0132] ⑴ Provide an anode and clean and dry the anode.

[0133] ⑵ Place the anode in the molecular beam epitaxy equipment.

[0134] (3) Open the phosphine valve and adjust the temperature in the molecular beam epitaxy equipment to 1000° C. to decompose the phosphine into phosphorus gas.

[0135] (4) Adjust the temperature in the molecular beam epitaxy equipment to 400°C.

[0136] (5) Open the indium furnace and the bismuth furnace, and form an indium beam and a bismuth beam through the beam source furnace of the molecular beam epitaxy equipment and spray them onto the substrate. Specifically, by controlling the temperature of the beam source furnace of the molecular beam epitaxy equipment, the temperature of the indium furnace is controlled to 850°C, and the temperature of the bismuth furnace is controlled to 480°C.

[0137] ⑹ In 8×10 4 Pa pressure and phosphorus environment, InP was grown on the substrate at a growth rate of 10nm / min for 3min. 0.99 Bi 0.01 , to form a carrier injection layer, wherein the thickness of the carrier injection layer is 30nm.

[0138] ⑺Dissolve 10 mg of Bi(NO3)3, 30 mg of NH4VO3 and 5 mg of NaBO2 in 2 mol of nitric acid.

[0139] ⑻After stirring for 30 minutes, add 2g of urea and stir until it becomes a transparent liquid.

[0140] ⑼ Adjust the temperature to 90°C and stir for 24 hours.

[0141] ⑽After cooling to room temperature, filter to obtain a yellow precipitate of BiVO4 doped with boron with a doping mass percentage of 10 wt%.

[0142] ⑾ Wash and dry the yellow precipitate of BiVO4 doped with boron at a doping mass percentage of 10 wt %, and then dissolve it in an ethanol solution to form a carrier transport layer ink with a concentration of 8 mg / ml.

[0143] ⑿ Place the carrier transport layer ink with a concentration of 8 mg / ml on the InP 0.99 Bi 0.01 A carrier injection layer is formed to form a carrier transport layer, and the thickness of the carrier transport layer is 30 nm.

[0144] ⒀Prepare a red QD functional layer on the carrier transport layer.

[0145] ⒁Prepare an electron transport layer on the red QD functional layer.

[0146] ⒂Prepare a cathode on the electron transport layer and seal it with a cover plate.

[0147] Example 2

[0148] The difference between this embodiment and embodiment 1 is that:

[0149] In the step (4), the temperature in the molecular beam epitaxy equipment is adjusted from 400°C to 350°C.

[0150] In the step (5), the indium furnace and the bismuth furnace are opened, and an indium beam and a bismuth beam are formed by the beam source furnace of the molecular beam epitaxy equipment and sprayed onto the substrate, wherein the temperature of the indium furnace is controlled to 850°C and the temperature of the bismuth furnace is controlled to 500°C by controlling the temperature of the beam source furnace of the molecular beam epitaxy equipment.

[0151] In step (6), at 8×10 4 Pa pressure and phosphorus environment, InP was grown on the substrate at a growth rate of 10nm / min for 3min. 0.97 Bi 0.03 , to form a carrier injection layer, wherein the thickness of the carrier injection layer is 30nm.

[0152] Example 3

[0153] The difference between this embodiment and embodiment 1 is that step (3) is omitted.

[0154] In the step (5), the indium furnace, the bismuth furnace and the antimony furnace are opened, and the indium beam and the bismuth beam are formed by the beam source furnace of the molecular beam epitaxy equipment and sprayed onto the substrate, wherein the temperature of the indium furnace is controlled to 850°C, the temperature of the bismuth furnace is controlled to 480°C, and the temperature of the antimony furnace is controlled to 600°C by controlling the temperature of the beam source furnace of the molecular beam epitaxy equipment.

[0155] In step (6), at 5×10 4 Pa pressure and argon environment, InSb was grown on the substrate at a growth rate of 10nm / min for 3min. 0.99 Bi 0.01 , to form a carrier injection layer, wherein the thickness of the carrier injection layer is 30nm.

[0156] Example 4

[0157] The difference between this embodiment and embodiment 1 is that:

[0158] In the step (7), 10 mg of Bi(NO3)3, 30 mg of ethyl orthosilicate and 3 mg of NaBO2 are dissolved in 2 mol of nitric acid.

[0159] Example 5

[0160] The difference between this embodiment and embodiment 1 is that:

[0161] In the step (7), 0.8 mmol of Bi(NO3)3 is dissolved in 32 mL of 15% aqueous glycerol solution and recorded as the first solution; 11 mg of NaVO4 and 0.4 mg of sodium acetate are dissolved in 32 mL of deionized water and recorded as the second solution, and the second solution is slowly added to the first solution.

[0162] In the step (8), after stirring for 30 min, NaOH was added to adjust the pH to 6.

[0163] In the step (9), stirring is continued for 30 min to obtain a suspension.

[0164] In the step (⑽), after heating to 180° C. and maintaining for 8 hours, the mixture is naturally cooled to room temperature and filtered to obtain a carbon-doped BiVO4 precipitate having a doping mass percentage of 10 wt%.

[0165] Example 6

[0166] The difference between this embodiment and embodiment 1 is that:

[0167] In the step (7), 2.5 mmol of bismuth nitrate is dissolved in 2 mol / L concentrated nitric acid, and magnetic stirring is performed for 30 min to obtain a first solution; 2.5 mmol of ammonium metavanadate is dissolved in 2 mol / L ammonia solution, urea (CO(NH2)2) is added in a ratio of N to V of 1:10, and magnetic stirring is performed for 30 min to obtain a second solution, and the first solution is slowly added to the second solution.

[0168] In the step (8), after mixing, magnetic stirring is continued for 1 hour, NaOH is added dropwise to adjust the pH to 7, and ultrasonic treatment is performed for 30 minutes.

[0169] In the step (9), continue magnetic stirring for 1 hour to obtain a suspension.

[0170] In the step (⑽), after heating to 180° C. and maintaining for 8 hours, the mixture is naturally cooled to room temperature and filtered to obtain a nitrogen-doped BiVO4 precipitate having a doping mass percentage of 10 wt%.

[0171] Comparative Example 1

[0172] The difference between Comparative Example 1 and Example 1 is that:

[0173] A PEDOT:PSS film was formed on the anode by a solution method as a carrier injection layer.

[0174] A TFB film is formed on the carrier injection layer by a solution method as a carrier transport layer.

[0175] Comparative Example 2

[0176] The difference between Comparative Example 2 and Example 1 is:

[0177] InP 0.99 Bi 0.01 A TFB film is formed on the carrier injection layer as a carrier transport layer.

[0178] Comparative Example 3

[0179] The difference between Comparative Example 3 and Example 1 is that:

[0180] A PEDOT:PSS film was formed on the anode by a solution method as a carrier injection layer.

[0181] Test result analysis:

[0182] The performance test of the light-emitting devices obtained by the preparation methods of Examples 1 to 6 and Comparative Examples 1 to 3 was carried out. Under the premise of the same brightness of 1000 nit, the EQE was calculated by measuring the brightness and current using an IVL optical measuring instrument, wherein EQE is the ratio of device excitons converted to photons. The life span (LT95) of the light-emitting device was measured using a life span aging device. The test results are shown in Table 1 below:

[0183]

[0184]

[0185] Table 1

[0186] It can be seen from Table 1 above that as the atomic ratio of the bismuth element in the carrier injection layer increases, its EQE becomes larger and the lifespan is increased. When the carrier injection layer adopts an indium III-V group compound doped with bismuth and / or the carrier transport layer adopts a bismuth-based layered compound doped with boron, the EQE of the light-emitting device changes slightly, but the lifespan is significantly increased.

[0187] In addition, the lifespan (LT95) of the light emitting devices of Example 1 and Comparative Example 1 were measured using a lifespan aging device, and a curve chart was drawn, as shown in FIG. Figure 5 As shown, according to Figure 5 It can be seen from the life curve that when the carrier injection layer adopts the indium III-V group compound doped with bismuth element and the carrier transport layer adopts the bismuth-based layered compound doped with boron element, the service life is significantly improved, and the turn-on voltage of Example 1 is lower than the turn-on voltage of Comparative Example 1, wherein the turn-on voltage is the voltage value when the brightness of the light-emitting device is 1nit, and the lower the turn-on voltage, the better the carrier recombination.

[0188] To sum up, the carrier injection layer of the embodiment of the present application adopts an indium III-V compound doped with bismuth element and the carrier transport layer adopts a bismuth-based layered compound doped with boron element to form a carrier functional layer, which can improve the carrier transport efficiency and increase the carrier recombination of the light-emitting device on the one hand, and on the other hand, it can also increase the service life of the light-emitting device.

[0189] Obviously, the embodiments described above are only some embodiments of the present application, rather than all embodiments. The preferred embodiments of the present application are given in the accompanying drawings, but they do not limit the patent scope of the present application. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification and drawings of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.

Claims

1. A composite film, characterized in that: comprising a first film and a second film which are stacked; The material of the first film is selected from a IIIA-VA compound doped with a first doping element, wherein the chemical formula of the IIIA-VA compound doped with the first doping element is A a T 1-b X b , wherein A is a group IIIA element, T is a group VA element, X is a first doping element, and 0<a≤1,0.01≤b≤5, wherein the first doping element is a main group element; The material of the second film is selected from a bismuth compound doped with a second doping element, wherein the chemical formula of the bismuth compound doped with the second doping element is Bi X M y O z , wherein Bi is a bismuth element, M is a second doping element, O is an oxygen element, and 1≤x≤3, 0<y≤1, 1<z≤6, wherein the second doping element is a main group element.

2. The composite film according to claim 1, characterized in that The atomic radius of the second doping element is less than 1 angstrom; and / or, The doping mass percentage of the second doping element is 1 to 10 wt %; and / or, The thickness of the first film is in the range of 30 to 50 nm; and / or, The thickness of the second film is in the range of 30 to 50 nm.

3. The composite film according to claim 1 or 2, characterized in that: The IIIA-VA Group compound is selected from at least one of InP, InAs, InSb, AlN, AlP, AlAs, AlSb, GaN, GaP, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, GaNP, GaNAs, GaPAs, GaPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNAs, GaAlN, GaAlPAs, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, and InAlNP; and / or, The first doping element is bismuth; and / or, The second doping element is selected from Group IIIA elements, and the Group IIIA element is selected from one of boron, aluminum, gallium, indium, and thallium.

4. A method for preparing a composite film, characterized in that: The following steps are involved: providing a substrate; Providing a first ink, and forming a first thin film on the substrate by using the first ink, wherein the first ink comprises a IIIA-VA group compound doped with a first doping element and a solvent; A second ink is provided, and a second thin film is formed on the first thin film by using the second ink, wherein the second ink includes a bismuth-based compound doped with a second doping element and a solvent.

5. The method for preparing a composite film according to claim 4, characterized in that: Forming a first thin film on the substrate using the first ink comprises: adding a bismuth salt, a second doping element compound and a substituting element compound into a reaction solvent to form a bismuth-based compound precursor solution doped with the second doping element; After the first treatment, a bismuth compound precipitate doped with the second doping element is obtained; dissolving the bismuth-based layered compound precipitate doped with the second doping element in a solvent to form a second ink; A second thin film is formed on the first thin film using the second ink.

6. The method for preparing a composite film according to claim 5, characterized in that: The step of adding the bismuth salt, the second doping element compound, and the substituting element compound into a reaction solvent to form a doped bismuth compound precursor solution specifically includes: dissolving the bismuth salt, the second doping element compound, and the substituting element compound in an acidic solution to form a mixed solution; adding an alkaline solution to the mixed solution and stirring the mixed solution until it becomes a transparent liquid to form a bismuth-based compound precursor solution doped with a second doping element; or, dissolving a bismuth salt in an organic solvent to form a first solution; Mixing the second doping element compound, the substituting element compound and the polar solvent to form a second solution; After the first solution and the second solution are mixed, an alkaline solution is added to the mixed solution to form a bismuth-based compound precursor solution doped with the second doping element.

7. The method for preparing a composite film according to claim 6, characterized in that: The bismuth salt is selected from at least one of bismuth phosphate and bismuth sulfate; and / or, The substituent element compound is selected from a vanadium compound and a silicon compound; and / or, The second doping element compound is selected from a boron compound, an aluminum compound, and a gallium compound; and / or, The solvent is selected from at least one of methanol, ethanol, ethylene glycol, glycerol, butanol, DMF, and DMSO; and / or, The organic solvent is selected from at least one of a glycerol aqueous solution and concentrated nitric acid; and / or, The polar solvent is selected from at least one of deionized water and ammonia water; and / or, The alkaline solution is selected from at least one of sodium hydroxide solution, potassium hydroxide solution or lithium hydroxide.

8. A light emitting device, characterized in that: comprising an anode layer, a composite film layer, a light-emitting layer, and a cathode layer stacked in sequence; or comprising an anode layer, a light-emitting layer, a composite film layer, and a cathode layer stacked in sequence; or It includes an anode layer, a composite film layer, a light-emitting layer, a composite film layer, and a cathode layer stacked in sequence; Wherein, the composite film layer is prepared by the composite film described in any one of claims 1 to 3 or by the method for preparing the composite film described in any one of claims 4 to 7.

9. The light emitting device according to claim 8, characterized in that: The material of the anode layer and / or cathode layer includes one or more of metal, carbon material and metal oxide, the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes doped or undoped metal oxide, including one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or, The light-emitting layer is a quantum dot light-emitting layer or an organic light-emitting layer; wherein the material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are respectively selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, wherein the II-VI group compounds include but are not limited to CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, Cd One or more of SeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and Group IV-VI compounds include but are not limited to SnS, SnSe, Sn Te, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, III-V compounds include but are not limited to GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, One or more of AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is, but is not limited to, at least one of CuInS2, CuInSe2 and AgInS2;The material of the organic light-emitting layer includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diarylanthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives.; 10. A display device, characterized in that: Comprising the light emitting device as claimed in claim 8 or 9.